Mothers' Knowledge About Basic Immunisation in Infants - Ernawati, Ernawati (Advances in Healthcare Research, 2023)
Purpose: This study aims to determine the level of mothers' knowledge about primary immunization for infants in the working area of Puskesmas Kassi-Kassi Makassar City. Research Design and Methodology: This study used a quantitative method with a descriptive approach. Data were collected by distributing questionnaires to 37 mothers with babies aged 0-12 months who visited the Kassi-Kassi Health Centre in February 2023. The sampling technique was accidental sampling. Findings and Discussion: The results showed that most mothers had a good understanding of primary immunization, including its definition, purpose, and benefits. The level of education and access to adequate information significantly influenced this knowledge. Most respondents knew that immunization protects infants and children against tuberculosis, pertussis, hepatitis, measles, and poliomyelitis. However, some mothers still lack adequate knowledge, which is often caused by low educational levels and limited access to information. Implications: This study makes a significant contribution to the field of public health by demonstrating the relationship between education level, access to information, and mothers' knowledge of immunization. These results can inform the development of more effective health education policies and programs. This study also emphasizes the importance of ongoing support from healthcare workers in offering counseling on primary immunization. Further efforts are needed to improve mothers' immunization knowledge through intensive and comprehensive extension programs.